The Intersection of Trauma and Criminal Law: A Forensic Psychology Approach to Women Victims of Domestic Violence — Literature Review - Nur Syifa Zakiah; Muhammad Ulil Albab; Jefri Firnando (Journal Psikologi Forensik Indonesia, 2025)
Domestic violence against women often results in profound psychological trauma, such as post-traumatic stress disorder (PTSD) and depression. The criminal justice system is often insensitive to the trauma experienced by victims, which worsens their condition during the legal process. This study aims to examine the relationship between psychological trauma due to domestic violence and the response of the criminal justice system, as well as the role of forensic psychology in supporting victim recovery. The research method used is a literature study, by analyzing relevant articles on domestic violence, psychological trauma, and the application of forensic psychology in the criminal law system. The results of the study show that the integration of forensic psychology in handling domestic violence cases can help understand the psychological impact of victims and improve the treatment of them in the legal process. The implications of this research are the importance of reforms in the criminal law system that are more responsive to the psychological trauma of victims, as well as the need for training for law enforcement officials to handle domestic violence cases with a more sensitive and humane approach.